Regionally-specific microglial activation in young mice over-expressing human wildtype alpha-synuclein - Watson, Melanie B.; Richter, Franziska; Lee, Soo Kyung; Gabby, Lauryn; Wu, Jennifer; Masliah, Eliezer; Effros, Rita B.; Chesselet, Marie-Françoise (Experimental neurology, 2012)
Parkinson's disease (PD) is characterized by widespread alpha-synuclein pathology and neuronal loss, primarily of the nigrostriatal dopaminergic neurons. Inflammation has been implicated in PD, and alpha-synuclein can initiate microglial activation; however, the kinetics and distribution of inflammatory responses to alpha-synuclein overexpression in vivo are not well understood. We have examined the regional and temporal pattern of microglial activation and pro-inflammatory cytokine production in mice over-expressing wild-type human alpha-synuclein driven by the Thy1-promoter (Thy1-aSyn mice). An increased number of activated microglia, and increased levels of TNF-α mRNA and protein were first detected in the striatum (1month of age) and later in the substantia nigra (5–6months), but not the cerebral cortex or cerebellum; in contrast, IL-1β and TGF‐β remained unchanged in the striatum and substantia nigra at all ages examined. Microglial activation persisted up to 14months of age in these regions and only minimal increases were observed in other regions at this later age. Increased concentrations of serum TNF-α were observed at 5–6months, but not at 1month of age. The expression of toll-like receptors (TLRs) 1, TLR 4 and TLR 8, which are possible mediators of microglial activation, was increased at 5–6months in the substantia nigra but not in the cerebral cortex, and TLR 2 was increased in the substantia nigra at 14months of age. With the exception of a slight increase in the striatum of 14month old Thy1-aSyn mice, MHCII staining was not detected in the regions and ages examined. Similarly, peripheral CD4 and CD8-postive T cells were increased in the blood but only at 22months of age, suggesting later involvement of the adaptive immune response. These data indicate that, despite the presence of high levels of alpha-synuclein in other brain regions, alpha-synuclein overexpression caused a selective early inflammatory response in regions containing the axon terminals and cell bodies of the nigrostriatal pathway. Our results suggest that specific factors, possibly involving a regionally and temporally selective increase in TLRs, mediate alpha-synuclein-induced inflammatory responses in the SN, and may play a role in the selective vulnerability of nigrostriatal dopaminergic neurons in PD. ► Mouse model of PD that overexpresses alpha synuclein show microglial activation. ► Microglial activation occurs early and is progressive with age. ► Microglial activation is confined to the striatum and substantia nigra. ► The pro-inflammatory cytokine TNF-alpha is increased with microglia activation. ► Toll-like receptors are increased in substantia nigra and may activate microglia.